Presentation: Conflicts in the Andes - Bolton, Ralph (1974)
In addition to journalists, novelists have tried to describe the struggles that occur in the Andean environment, especially the difficulties between neighboring communities and between communities and haciendas. In this sense, the works of Ciro Alegría, José María Arguedas, and Manuel Scorza stand out, to mention only three authors.